2015
DOI: 10.3390/s150923249
|View full text |Cite
|
Sign up to set email alerts
|

A Palladium-Tin Modified Microband Electrode Array for Nitrate Determination

Abstract: A microband electrode array modified with palladium-tin bimetallic composite has been developed for nitrate determination. The microband electrode array was fabricated by Micro Electro-Mechanical System (MEMS) technique. Palladium and tin were electrodeposited successively on the electrode, forming a double-layer structure. The effect of the Pd-Sn composite was investigated and its enhancement of catalytic activity and lifetime was revealed. The Pd-Sn modified electrode showed good linearity (R2 = 0.998) from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…[105] This sensor was able to detect nitrate in the range of 1 mg L -1 to 20 mg L -1 with a sensitivity of 398 µA/(mg L -1 cm 2 ). [105] Most recently, the same group developed a chemical sensor for nitrate detection based on an ultramicro IDA modified by Pd-AuNPs. [106] The sensing layer (Pd-AuNPs) was electrodeposited on the electrode surface and showed a good linearity from 1 mg L -1 to 15 mg L -1 in neutral water conditions.…”
Section: Chemical Sensorsmentioning
confidence: 99%
See 3 more Smart Citations
“…[105] This sensor was able to detect nitrate in the range of 1 mg L -1 to 20 mg L -1 with a sensitivity of 398 µA/(mg L -1 cm 2 ). [105] Most recently, the same group developed a chemical sensor for nitrate detection based on an ultramicro IDA modified by Pd-AuNPs. [106] The sensing layer (Pd-AuNPs) was electrodeposited on the electrode surface and showed a good linearity from 1 mg L -1 to 15 mg L -1 in neutral water conditions.…”
Section: Chemical Sensorsmentioning
confidence: 99%
“…Xia and his co-workers reported several papers on the analysis of water based on microband electrode arrays. [104][105][106] In one, a microsensor based on gold microband array for the determination of phosphate in fresh water was fabricated where gold nanoparticles (AuNPs) were deposited on the electrode surface to improve the sensitivity. [104] The fabrication process and the structure of the electrode is shown in Figure 15; the modified electrode gave a sensitivity of 7.66 µA per (mg P.L) which is three time larger than the unmodified electrode.…”
Section: Chemical Sensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…When studies were carried out with Pt-loaded SnO 2 and Pd-doped SnO 2 , the latter was found to be more selective for hydrogen giving a fast response [54]. The sensitivity and life-time was shown to be higher for Pd-tin reformed microband electrode series, as a nitrate sensor [55]. The sensors using Pd-doped TiO 2 fibers exhibited encouraging gas sensing characteristics like low operation temperature and adequate gas response [56].…”
Section: Real-time Testing Of the Sensormentioning
confidence: 99%